PEMBELAJARAN BAHASA INDONESIA MENYENANGKAN DAN BERKARAKTER - Yusuf, Yusron (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2016)
Based on findings of literature study, a pleasing, delightful, as well as unique Learning on Bahasa can be summed up as follows: (1) delightful learning needs various methods such as interactive learning, learning by doing, indirect learning, as well as effective direct one; (2) Character building should teach moral nature, sincerity, responsibility; (3) Methods of Character Building include: exemplary, simulation (experiential learning), icon method and affirmation (sticking and hanging), power repeat method, 99 excellent character method, Values of excellence building, as well as metaphor usage. Keywords: delightful learning, character building, methods